Steelband Running Wild in Mih Head - Smith, Keith (Daily Express)
The article looks at whether Solo Harmonites will become the first band ever to win the finals of the Panorama competition playing its own tune. While in recent years a number of steelbands have submitted their own tunes to the judges' ears, they have met with varying degrees of success, but have not taken the big prize.
Keywords: Steel bands (Music) -- Competitions -- Trinidad and Tobago; Steel band music -- Trinidad and Tobago; Popular music -- Trinidad and Tobago